Nilai-Nilai Pendidikan Karakter dalam Al-Qurān (The Value of Character Education in The Qur’an) - Musthofa Musthofa (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2020)
The values ​​of character education based on teachings that originate from the Qur'an are called the values ​​of character education in the’Qur'an. This article is presented sourced from data obtained from the literature sourced from the Qur'an, Al-Hadith and the opinions of experts relating to this discussion. This article is analyzed using the Izwaji Tafsir description method, based on the Qur'an, Al-Hadith and the opinions of experts. This article discusses the formation of the character values ​​of the Qur'an in two ways, namely: First, Fāid, namely the abundance of God's gifts in the form of Al-Qur'an character values ​​(honest, fair, patient, thankful, zuhud, devoted, humble, humble, self-control) to someone Allah wants. Second, Iktisābah, namely the formation of character through human effort, including: (1) Introduction, (2) Understanding, (3) Application, (4) Habit, (5) Compliance, (6) Cultivation, (7) Realizing the character, to form the values ​​of character education are in accordance with the character of the Qur'an.